Desarrollo de un modelo de responsabilidad social como ventaja competitiva para la empresa Quito Motors S.A.C.I. ubicada en la provincia de Pichincha cantón Quito - Armas Chamorro, Eliana Maricela (2015)
The following research paper presents the development of a model of social responsibility as a competitive advantage for the company Quito Motors S.A.C.I., dedicated to the merchandising of vehicles and their preventive and corrective maintenance, Quito Motors is representative of the Ford brand to the Sierra region of Ecuador. Chapter 1 includes a historical overview of the company and its current stage, detailing its organizational structure and identifying the difficulties inclusive antecedents that the company has with the social responsibility. In chapter 2 several concepts already established in the field of Social Responsibility and its importance within organizations are analyzed, also the classification and entities that venture and help the implementation and development of a socially responsible management are studied. In chapter 3 it realized an analysis of recompilation data tools, which let us know the expectations the company has with the implementation of a gestion model of social responsibility. In chapter 4 it represents a model based on the four pillars of the brand and classification of social responsibility, further activities and responsibilities that must make to become a socially responsible company are established.